Drosophila Ubiquitin C-Terminal Hydrolase Knockdown Model of Parkinson's Disease. - Tran, H.H.; Dang, S.N.A.; Nguyen, T.T.; Huynh, A.M.; Dao, L.M.; Kamei, K.; Yamaguchi, M.; Dang, T.T.P. (Scientific reports, 2018)
Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide. Many factors have been shown to contribute to its pathogenesis including genetic and environmental factors. Ubiquitin C-terminal hydrolase L1 (UCHL1) is also known to be involved in the pathogenesis of PD. We herein modeled the study of UCHL1 in Drosophila melanogaster and investigated its functions in PD. The specific knockdown of the Drosophila ortholog of UCHL1 (dUCH) in dopaminergic neurons (DA neurons) led to the underdevelopment and/or degeneration of these neurons, specifically in DL1 DA neuron cluster in the larval brain lobe and PPM2, PPM3, PPL2ab, and VUM DA neuron clusters in the adult brain. These defects were followed by a shortage of dopamine in the brain, which subsequently resulted in locomotor dysfunction. The degeneration of DA neurons in dUCH knockdown adult brain, which occurred progressively and severely during the course of aging, mimics the epidemiology of PD. DA neuron and locomotor defects were rescued when dUCH knockdown flies were treated with vitamin C, a well-known antioxidant. These results suggest that dUCH knockdown fly is a promising model for studying the pathogenesis and epidemiology of PD as well as the screening of potential antioxidants for PD therapeutics.